HUBUNGAN PERSONAL HYGIENE IBU MENYUSUI DENGAN TINGKAT KEJADIAN DIARE PADA BAYI DI KELURAHAN SITIREJO 1 MEDAN KOTA - Purba, Bahtera David; Silalahi, Novrika; Malau, Pitto Pratiwi; Sembiring, Ripando; Kembaren, Efrata (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2024)
Diarrhea is a change in the shape and consistency of stools that are soft to liquid, defecate more than usual, namely 3 or more times a day. Diarrhea is the second leading cause of death in children under five years and kills around 760,000 children every year. Based on the percentage distribution of mortality in the world, diarrhea is still the main cause of death in infants by 15%. This type of research was an observational district with a cross-sectional approach which was carried out for 6 months starting from February in 2023. It was carried out in the Sitirejo 1 sub-district area of ​​Medan Kota. The sampling method used was using the Lemeshow and Iwanda formulas, so a sample of 51 breastfeeding mothers used univariate and bivariate analysis. The results showed that the age of most breastfeeding mothers was 21-30 years old 72.5%, at work the most respondents were housewives 58.8% of respondents and the most recent education was elementary school as many as 43.1% of respondents. In the cleanliness of the mother's nipples, 43 respondents (84.3%) were in the unclean category and produced a p=value of 0.001, in the mother's hand washing habits, 38 respondents (74.5%) did not wash their hands with a p=value of 0.013, 41 respondents (80.4%) opened baby clothes in the open category with a p=value of 0.027, 42 respondents (82.4%) opened baby food storage areas with a p=value of 0. 013, the cleanliness of the floor is included in the category of unclean as many as 39 respondents (76.5%) with a p=value of 0.011. So it can be concluded that the cleanliness of the mother's nipples, the place for storing baby clothes, the place for storing baby food and the cleanliness of the floor has a relationship with the incidence of diarrhea, therefore it is necessary to provide counseling, training and supervision that meets the mother's personal hygiene standards.